Archaeology, anthropology and the stuff of time. (15th May 2015) - Yarrow, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> Lucas's discussion of contemporaneity makes an important contribution to archaeological understandings of chronology and dating and to broader debates about temporality. Extending his earlier work on time (Buchli and Lucas 2001; Lucas 2001; 2005), Lucas's central insight is that contemporaneity is not a function of a shared unit of time but of the specific relations through which objects are imbricated. The approach is likely to have profound implications for archaeological approaches to chronology. Whether or not it undermines the current preoccupation with absolute dating, it should certainly give renewed impetus to those branches of archaeology that make it possible to examine time as a matter of the specific material properties of artefacts. This is important, first, because it opens up the possibility of more nuanced empirical understanding of the very stuff of time (literally how it is materially manifest) and, second, because such empirical understandings enable conceptual refinement and extension of the categories through which time is understood. Of broader interest for non-archaeological readers are the ramifications of this discussion of contemporaneity for the ways in which time is investigated and conceptualized. Writing as an anthropologist, interested but with no expertise in archaeological dating, it is these latter considerations that I want to pursue in my comments, as these relate to contemporaneity and to the broader investigation of time.